A new arboreal lizard of the genus Celestus (Squamata: Anguidae) from Northern Honduras - McCranie, James R (1996)
A new species of arboreal lizard of the genus Celestus is deseribed from north-eentra1 Honduras. This new species appears to be most elosely related to C. bivittatus and is easily distinguished from that species by haying longer digits on both the fore- and hindlimbs.